Classification of Certain 6-Manifolds - Andrus, George Dennis (My University, 1977)
Oriented, simply-connected, differentiable 6-manifolds, with vanishing second Stiefel-Whitney class and integral homology groups H2(M)=H3(M)=Z/n, where nΞ0 mod 4, are shown to be classified up to orientation preserving diffeomorphism by the following invariants: the cohomology ring of M with coefficients in the ring Z/n, the first Pontrjagin class of the tangent bundle of M, and the Pontrjagin cubing cohomology operation.
Keywords: Mathematics; Mathematics